Biologically active compounds from two members of the Asteraceae family: Tragopogon dubius Scop. and Tussilago farfara L. - DOĞAN, AHMET; EMRE, GİZEM; ŞENKARDEŞ, İSMAİL (TAYLOR & FRANCIS INC, 2019)
Tragopogon dubius and Tussilago farfara are consumed as vegetables and used in folk medicine to manage common diseases. Herein, the chemical compositions and biological activities of different leaf extracts (ethyl acetate, methanol, and water) of T. dubius and T. farfara were evaluated. The antibacterial, antifungal, and antioxidant abilities of the extracts were tested using different assays including free radical scavenging, reducing power, phosphomolybdenum, and metal chelating assays. Enzyme inhibitory potentials were evaluated against cholinesterases, tyrosinase, alpha-amylase and alpha-glucosidase. Complexes of bioactive compounds (chlorogenic and rosmarinic acid) were docked into the enzymatic cavity of alpha-glucosidase and subjected to molecular dynamic calculation, enzyme conformational stability, and flexibility analysis. T. dubius and T. farfara extracts showed remarkable antioxidant potentials. Ethyl acetate extracts of T. dubius and T. farfara were the most potent inhibitors of acetylcholinesterase and butyrylcholinesterase. T. dubius ethyl acetate extract and T. farfara methanolic extract showed noteworthy activity against alpha-glucosidase. High performance liquid chromatography analysis revealed the abundance of some phenolic compounds including chlorogenic and rosmarinic acids. Ethyl acetate extract of T. dubius showed notable antifungal activity against all strains. Docking studies showed best pose for chlorogenic acid was stabilized by a network of hydrogen bonds with residues Asp1157, Asp1279, whereas rosmarinic acid showed several hydrogen bonds with Asp1157, Asp1420, Asp1526, Lys1460 and Trp1369. This study further validates the use of T. dubius and T. farfara in traditional medicine, as well as act as a stimulus for further studies for future biomedicine development. Communicated by Ramaswamy H. Sarma
Keywords: T; dubius; T; farfara; polyphenols; antioxidant; enzyme inhibition; in silico studies; FLOWER BUDS; IN-VITRO; ANTIOXIDANT ACTIVITY; NATURAL-PRODUCTS; ANTIACETYLCHOLINESTERASE ACTIVITIES; NEURODEGENERATIVE DISEASES; PYRROLIZIDINE ALKALOIDS; INHIBITORY-ACTIVITIES; PHENOLIC-COMPOUNDS; OXIDATIVE STRESS